Seismic evaluation of old masonry buildings: performance and strengthening - Varum, H. (2012)
The concern and need to assess seismic vulnerability, particularly of the traditional masonry buildings under seismic actions is a key issue, that should be a priority in the mitigation of the seismic risk, definition of strengthening requirements needs and minimization of possible damages due to seismic actions, in the identification of critical buildings and safeguarding of built heritage. This paper provides information on the constructive and structural details of the traditional buildings in Coimbra, Portugal, and interprets the potential structural damage and discusses its seismic behaviour, identifying structural fragilities and consequently their vulnerability. It also presents the main results obtained in the numerical studies, and verifies the global stability and dynamic response to seismic actions. Three different strengthening techniques to improve the global behaviour of these buildings were modelled and analysed. Efficiency of the strengthening strategies is also discussed in terms of deformation demands and cost-benefit analysis.